LA VALUACIÓN DE EMPRESAS EN EL DERECHO CONCURSAL DE MÉXICO Y DE LOS ESTADOS UNIDOS DE AMÉRICA - Martínez Miranda, Elio Agustín (UNIVERSIDAD DE SONORA, 2023)
Abstract The objective of this research is to address the business valuation within the bankruptcy proceedings, carrying out a comparative law exercise, that is, contrasting what is established by the Mexican Bankruptcy Law (Ley de Concursos Mercantiles) and the United States Bankruptcy Code, in conjunction with the practice carried out in both countries on this issue. Therefore, based on this comparison, legal and financial elements are provided within the business valuation, which could help to strengthen the bankruptcy proceedings in Mexico.